Optimization of NdFeB alloy composition for preparing high-performance melt-spun ribbons - Nguyen, Xuan Truong; Vu, Hong Ky; Vuong, Kha Anh; Nguyen, Hoai Nam; Dang, Thi Thuy Ngan; Nguyen, Huy Hoang; Nguyen, Van Vuong (Communications in Physics, 2024)
The magnetic field assisted melt-spinning method is a novel approach for producing anisotropic NdFeB-based ribbons and anisotropic bonded magnets. These anisotropic ribbons are required to be grown on the magnetized seeds, so the initial composition of the alloys used for melt-spinning ribbons is very crucial in creating ribbons’ textured microstructures. This paper reveals the results concerning the choice of alloy compositions containing Nd, Fe, Co and B to optimize the processing of ribbons with the high texture degree, high spontaneous magnetization, large coercivity as well the strong exchange-coupling interaction. The guides of producing these ribbons are presented in detail that are fruitful in a massive production of high-performance NdFeB-based anisotropic ribbons and magnets prepared thereof.